Prinsip Kesantunan Berbahasa pada Novel Pertemuan Jodoh Karya Abdoel Moeis: Tinjauan Pragmatik - Usada, Sinnta (University of Brawijaya, 2025)
This research is motivated by problems regarding the principles of language politeness in a literary work. The aim of this research is to reveal the principles of language politeness built by writers in a literary work, especially in dialogue using the pragmatics of Leech language politeness. The research method was carried out descriptively qualitatively, the object was content in the novel Meeting Jodoh by Abdoel Moeis. The findings show that as many as 19 speech data comply with the six principles of language politeness according to Leech, and as many as 8 speech data violate the six principles of language politeness according to Leech. Thus, it can be concluded that this novel was written while still paying attention to the principles of language politeness, even though the author provides a novel theme that is free in language (there is a mixture of foreign languages and Indonesian)